The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/inf.0b013e3182a735ed
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Insufficiency in HIV-infected Children and Young Adults

Abstract: VDD and VDI were common in both HIV-infected and control groups, and serum 25(OH)D concentrations were significantly lower in controls than in HIV-infected children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Interactions with HIV serostatus were explored and none were found to be significant in adjusted models, with the exception of the effect of 25[OH]D on 1, 25[OH] 2 D as described below. The vitamin D deficiency prevalence of 41% observed among HIV-infected men in this sample of MACS lies in the middle of a very wide range of prevalence estimates (10%-83%) reported in other studies of HIV-infected individuals 16,20,[35][36][37] and is consistent with the 39% prevalence reported in the general population. 16 The wide range of vitamin D deficiency prevalence estimates in HIV infected likely results from differences in demographics, geographic location, seasonality, and other study population characteristics as well as varying definitions of vitamin D deficiency.…”
Section: Determinants Of 25[oh]d Statussupporting
confidence: 76%
“…Interactions with HIV serostatus were explored and none were found to be significant in adjusted models, with the exception of the effect of 25[OH]D on 1, 25[OH] 2 D as described below. The vitamin D deficiency prevalence of 41% observed among HIV-infected men in this sample of MACS lies in the middle of a very wide range of prevalence estimates (10%-83%) reported in other studies of HIV-infected individuals 16,20,[35][36][37] and is consistent with the 39% prevalence reported in the general population. 16 The wide range of vitamin D deficiency prevalence estimates in HIV infected likely results from differences in demographics, geographic location, seasonality, and other study population characteristics as well as varying definitions of vitamin D deficiency.…”
Section: Determinants Of 25[oh]d Statussupporting
confidence: 76%
“…Subjects receiving tenofovir did not differ at baseline or in the change in 25 In a few studies evaluating children and young adults with HIV infection, researchers found a high prevalence of suboptimal 25(OH)D, ranging from 71% to 89% <30 ng/mL [3,[26][27][28]] to 33% to 78% <20 ng/mL [1,4,[29][30][31], with 1 group reporting 87% <15 ng/mL [2]. Our results support the finding that suboptimal 25(OH)D status is common in unsupplemented youth, with 95% at baseline having a 25(OH)D <32 ng/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D status may be more important to characterize in HIV-infected children/youth, as peak bone mass is not attained until age 25. The prevalence of 25(OH)D < 30 ng/mL in perinatally-infected children and young adults on ART was 43% in Thailand(27*), but reported in 96% in a Parisian cohort(28). In the US, 87% of behaviorally-infected(1) and 56% of perinatally-infected(29) children and young adults had 25(OH)D < 15 ng/mL.…”
Section: Vitamin D Deficiency In Hivmentioning
confidence: 99%